Regulação e supervisão das fintechs nos mercados financeiro da União Europeia - Lumango, José Francisco (2020)
This research aims to identify the challenges of regulation and supervision of fintechs in the European Union in the financial markets, a reality stimulated by technological innovation that is revolutionizing financial innovation. The discovery of new ways to regulate new financial products and services puts at risk two essential goals for their survival: the first is the possibility of financial innovation eliminating financial intermediation, jeopardizing one of the main sources of profitability for banks; and the second is the risk that the State, as a regulatory body, will have reduced access to the records of financial transactions. The approach was developed within the scope of regulatory law, framing the financial crisis of 2008, and the technological revolution and financial innovation that affects the financial system. The new realities such as fintechs, bitcoins and blockchains, are changing the paradigms of regulation and supervision, whose answer can be given through Disruptive Regulation, a concept that brings together regtechs and supetechs as a new way of looking at the technological revolution and the financial innovation. The focus on regulating disruptive technologies that stimulate innovation in the financial markets brings with them new regulatory alternatives such as Regulatory Sandboxes, Innovation Hubs, accelerators and incubators for startups dedicated to the experimentation process (application, preparation, testing and evaluation). These new realities also pose complex challenges for regulators, such as the high risk of hacking, the risk of information asymmetry and the difficulty of accountability in case of errors in machines, software and humans. This set of regulatory alternatives supported by suptechs and regtechs is called Disruptive Regulation.